7x-4=x+2 7x=x+2+4 7x=x+6 7x-x=6 6x=6 X=1
7X-1=9+5X. add 1 to both sides 7X=10+5X. Subtract 5X and get 2X=10 divide by 2 and x=5
4xy+1=3y-7x 4xy-3y=-7x-1 y(4x-3)=-7x-1 y=(-7x-1)/(4x-3)
1 - 5x + 7x is an expression, not an equation (no equals sign), so you cannot solve for x. You can, however simplify (combine like terms) and get 1 + 2x.
2y + 7x + y-1?
This is not possible to "solve" as such. 3x + 4x = 7x, which is the same as 7x=7x. Clearly, you end up with x=x, which is true, but not useful.This suggests that you have used the wrong method when trying to solve the problem, however your algebra was correct, since x does indeed equal x; it's when you end up with something like 2=1, or 1=0, that you have to worry.
2x + 5x - 1 = 9x 7x - 1 = 9x -1 = 9x - 7x -1 = 2x -1/2=x
7x+2 = 3x-2 7x-3x = -2-2 4x = -4 x = -1
its pretty easy: 3-2 = 1 so if u multiply 1 x 7x, it equals 7x
-3x - 1 = 20 + 4x 1) the first thing you want to do is have the variable(x) in one side of the equation. so subtract so add -3x to 4x. -1 = 20 + 7x 2) now you want to isolate the variable so subtract 20 to -1. -21 = 7x 3) to solve for x you need to divide by 7 on both sides and 7x divided by 7 is one or just x and whatever you do to one side you must do to the other -21 divided by 7 is -3 x = -3
22=7x+1 (take 1 of each side of the equals) 21=7x (divide each side by seven) 3=x (BAM! answer)
7x + 8
-4x-1-3x-4+5 = -7x-1-2x+1+6 -7x = -9x+6 2x = 6 x = 3
22 - 7x = 0 /+7x 22 = 7x /divide by 7 x = 22/7 = 3 1/7 22/7 is your more formal answer, that's pertaining what's asked for the question, is it to answered as a mixed fraction, or improper fraction.
1 divided by 13 equals 13
Anything divided by itself equals one.
It is: y = -7x+1 in slope intercept form
combine like terms. 3x+1+4x-5=31 3x+4x=7x 7x+1-5=31 1-5=-4 7x-4=31 then solve it 7x=35 x=5
It is solved when you have it in the form of (x = some number). In this case, you have 7x on one side, which is 7 times x. You need to divide both sides by 7, so you have: 7x / 7 = 7/7. On the left side, this becomes x. On the right side 7/7 = 1, so x=1 solves the equation. If you 'plug in' x=1 to the original equation, you get 7(1) = 7, or 7 times 1 equals 7, which is true.